Manajemen Santri di Masa Pandemi (Studi Kasus di Pondok Pesantren Lirboyo Cabang IV Santren Blitar) - Nila Lukmatus Syahidah (Journal of Islamic Education Management)
The condition of students who live in Islamic boarding schools during the pandemic requires a way to facilitate them to continue to study and carry out their activities safely. For this reason, it is necessary to investigate the methods used by managers in carrying out student management so that students can continue to participate in Islamic boarding school activities and programs and avoid exposure to COVID-19. The researcher applied a qualitative approach, with data collection techniques in the form of observation, interviews, and documentation, as well as applying triangulation techniques to check the validity of the data. Managers carry out student management to achieve learning goals and achieve the goals of Islamic boarding schools, as well as trying to prevent students from being exposed to COVID-19. The manager places the goals of institutions and government regulations as guidelines for the management of students, including 1) managing the daily schedule of students, 2) managing learning activities, 3) managing the health of students, according to applicable regulations.